MAKNA TINDAK TUTUR DIREKTIF DALAM KOMIK NORAGAMI KARYA ADACHITOKA - Putu Apriani; Betty Aritonang; Ni Wayan Meidariani (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2021)
This research focuses on the meaning of directive speech acts uttered by the characters in the Noragami comic. The data source used in this research is dialogue spoken by the characters in the Noragami comic, which was first released in 2011 by Adachitoka.The purpose of this study was to determine the meaning of directive speech acts contained in the comic Noragami by Adachitoka.The method used in this research is the documentation method with reading and note-taking techniques. The method and data analysis technique used in this study were qualitative methods and were further analyzed using Dell Hymes' speech event theory.Methods and techniques for presenting the results of data analysis used in this study are informal methods. The results of the analysis in this study found that directive speech acts in the comic Noragami by Adachitoka have the meaning of ordering, asking, encouraging and prohibiting.